Analysis of Criminal Law and Islamic Criminal Law on Sanctions for Justice Collaborators: Brigadier Joshua Murder - Nasution, Putri Dayani; Harahap, Marie Mahfudz (Jurnal Ilmu Hukum Kyadiren, 2024)
This research examines the role of justice collaborators in murder cases under Indonesian positive law and Islamic criminal law, focusing on the case of Brigadier Joshua’s murder. The study analyzes the regulations for criminal sanctions applied to justice collaborators and explores how Islamic law views such sanctions. The research employs a normative methodology with a comparative approach, utilizing secondary data sources. The findings reveal that while Indonesian law provides for leniency in sentencing justice collaborators, the specific reduction is left to judicial discretion. In the case study, Bharada Richard Eliezer received a significantly reduced sentence for his cooperation. Islamic law similarly allows for forgiveness and sentence reduction, particularly in cases of qisas, diyat, and ta’zir punishments. The study concludes that both legal systems recognize the importance of justice collaborators in uncovering complex crimes, but lack specific regulations on sentence reductions. The authors recommend developing more comprehensive legislation to govern reduced sentences for perpetrator witnesses in both systems.